TUJUAN KURIKULUM PAI DALAM UNGANG-UNDANG PENDIDIKAN - Uswatun Hasanah (QATHRUNÂ, 2018)
Since the independence of Indonesian Republic until now , Islamic education continues to evolve with the times, Accommodation madrassah into the national education system became the forerunner of Islamic madrassah as education providers who are subject to the national education system, madrassah eventually modified into distinctively Islamic. At least three periods of the implementation of the National Education System Law in Indonesia since 1950 until now. Educational objectives formulated in the National Education Act, both Law No. 4 Year 1950 jo Law No. 12 of 1954 which created the human being educated Indonesia as "Humans are capable and democratic decency and responsibility about the welfare of society and the homeland" or Law No. 2 1989 idealize Indonesian fully human beings, the "man who is faithful and devoted to God Almighty and noble character, physically and mentally healthy, have the knowledge and skills, personality steady and independent and have a sense of civic responsibility and nationality", and the latter Act No. 20 of 2003 which aspires "man who is faithful, pious and noble, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible". Among the goals of education in education law in 1950, 1989 and 2003, there is a clear shift towards improvement.